Mind Map-Assisted STEM Integration to Enhance Students' Science Skills in the 21st Century: A Literature Review - Pradicta Nurhuda; Ruth Megawati; Sudirman; Risnawati Agustin (Postgraduate, University of Mataram, 2024)
Creative thinking skills help students develop new ideas and concepts, imagine, find interrelated relationships, and have multiple perspectives on something. If their creative thinking skills are lacking, students will face difficulties in solving problems or learning questions. Mind Mapping helps organize numbers, letters, words, ideas, concepts, and other items so that they are not lost shortly. This helps students understand and develop creative thinking in science learning in the 21st century. Where the purpose of the study is to examine the Integration of Mind MAP in STEM to Improve Students' Science Skills in the 21st Century: Literature Review. This review was conducted based on state-of-the-art methods using the guidelines for preferred reporting items for reviews and meta-analyses (PRISMA). The results of this study explain the Description of STEM Content (Science, Technology, Engineering, Mathematics); Benefits of the STEM Learning Method, namely (Improving Skills, Motivating Children, Self-Evaluation, Fun Learning, Important Pillars); Advantages of the Mind Mapping Learning Model (Can express opinions freely; Notes are more concise and clear; Easier to find notes if needed; Notes are more focused on the core material; Easy to see the overall picture; Disadvantages of the Mind Mapping Learning Model (It takes longer to